Solitary sacral osteochondroma growing into the spinal canal: Case report and review of the literature - Zhenni Yu; Zilin Zhao; Chao Deng; Yingwei Chen; Li Guan; Cong Huang (Radiology Case Reports, 2024)
Osteochondroma is one of the most common benign bone tumors, mainly involving the bone ends of long bones, and involving the spine is rare. It often involves the competing, followed by the thoracic and lumbar spine, and rarely involves the sacrum. We report the imaging findings of a solitary osteochondroma of the sacrum. The patient was a 37-year-old woman who presented clinically with progressive low back pain associated with left buttock pain and discomfort. CT and MRI showed that the lesion originated from the left lamina of S1 and grew anteriorly and superiorly, resulting in compressive resorption of the L5 vertebral bone, left foraminal stenosis and adjacent nerve root swelling. The patient underwent surgery and the mass was completely excised and recovered well postoperatively. Osteochondroma arising from the sacrum is rare and can lead to compressive resorption of adjacent bone, and imaging techniques are conducive to the localization and characterization of the lesion and provide useful information for clinical treatment.